Cutaneous Mycobacterium Abscessus Infection Following Plastic Surgery: Three Case Reports - Shen H; Zhang Q; Peng L; Ma W; Guo J (Dove Medical Press, 2024)
Hongwei Shen,1,* Qiaomin Zhang,1,* Liang Peng,2 Wen Ma,1 Jingdong Guo2 1Clinical Laboratory, Shenzhen Hospital of Southern Medical University, Shenzhen, Guangdong, People's Republic of China; 2Department of Burns and Plastic Surgery, Shenzhen Hospital of Southern Medical University, Shenzhen, Guangdong, People's Republic of China*These authors contributed equally to this workCorrespondence: Jingdong Guo; Hongwei Shen, Email guojingdong1996@163.com; hongweishen@smu.edu.cnAim: Mycobacterium abscessus is ubiquitous in the environment and seldom causes infections in immunocompetent individuals. However, skin and soft tissue infections caused by M. abscessus have been reported in recent years. Additionally, the cutaneous infections or outbreaks post cosmetic surgery caused by M. abscessus have been increasing due to the popularity of plastic surgery. The main modes of transmission are through contaminated saline, disinfectants, or surgery equipment, as well as close contact between patients. This article describes three patients who were admitted to our hospital between November 2019 and October 2020. They presented with long-term non-healing wounds caused by M. abscessus infection after undergoing plastic surgery. Symptoms presented by the three patients included swelling, ulceration, secretion, and pain. After identification of M. abscessus with Ziehl-Neelsen staining and MALDI-TOF MS system, the patients were treated with surgical debridement and clarithromycin.Conclusion: It is important to note that a long-term wound that does not heal, especially after plastic surgery, should raise suspicion for M. abscessus infection. The infection mechanism in these three patients may have been due to exposure to surgical equipment that was not properly sterilized or due to poor sterile technique by the plastic surgeon. To prevent such infections, it is important to ensure proper sterilization of surgical equipment and saline.Keywords: Mycobacterium abscessus, cutaneous infection, plastic surgery, treatment, antibiotic resistance